2019
DOI: 10.3390/cancers11050734
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering The Potential Role of Hox Genes in Pancreatic Cancer

Abstract: The Hox gene family plays an important role in organogenesis and animal development. Currently, 39 Hox genes that are clustered in four chromosome regions have been identified in humans. Emerging evidence suggests that Hox genes are involved in the development of the pancreas. However, the expression of Hox genes in pancreatic tumor tissues has been investigated in only a few studies. In addition, whether specific Hox genes can promote or suppress cancer metastasis is not clear. In this article, we first revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…In addition, we found that the expression levels of HOXA6 and HOXA10 were significantly high in AML. This result is similar to findings in lung adenocarcinomas [51], breast cancer [52] and prostate cancer [53]. However, no such evidence has been reported in AML.…”
Section: Kaplan-meier Survival Analysissupporting
confidence: 88%
“…In addition, we found that the expression levels of HOXA6 and HOXA10 were significantly high in AML. This result is similar to findings in lung adenocarcinomas [51], breast cancer [52] and prostate cancer [53]. However, no such evidence has been reported in AML.…”
Section: Kaplan-meier Survival Analysissupporting
confidence: 88%
“…HOX proteins function as oncogenes or tumour suppressors, depending on the context [4]. An increasing number of HOX proteins have been investigated in various tumours, including acute myeloid leukaemia [5], breast cancer [6], lung cancer [7], and digestive tract neoplasms [8][9][10]. Currently, the implications of HOX proteins in tumorigenesis and development of GC have been reported in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…15 Deregulation of HOX genes has also been identified in cancer. 1618 Several studies reported differences between normal and tumor conditions as reviewed by Bathlekar et al 12 and also the role of HOX genes in cancer susceptibility and progression; 19 however, assigning a specific role for HOX genes as drivers of the malignant phenotype requires further investigation. Evidence that HOX genes may be deregulated in different ways in different types of cancer is accumulating.…”
Section: Introductionmentioning
confidence: 99%